Back Cover Image, Volume 5, Number 2, February 2023. Issue 2 (17th February 2023) - Chen, Fuping; Di, Yujie; Su, Qiong; Xu, Dongming; Zhang, Yangpu; Zhou, Shuang; Liang, Shuquan; Cao, Xinxin; Pan, Anqiang
Abstract : Back cover image : Hard carbons are promising anode materials for sodium‐ion batteries. Developing appropriate strategies to expand the area of pseudographite carbon are urgently needed for increasing the low‐potential platform capacity. In article number 10.1002/cey2.191, Fuping Chen et al. prepared a series of vanadium‐modified hard carbon with sufficient pseudographitic domains and stable interface. The optimized hard carbon spheres modified by vanadium carbide exhibited high low‐potential plateau capacity and cycling stability.